Now you see it, now you don't: The context dependent nature of category-effects in visual object recognition - Gerlach, Christian; Toft, Kristian Olesen (Visual cognition, 2011)
In two experiments, we test predictions regarding processing advantages/disadvantages for natural objects and artefacts in visual object recognition. Varying three important parameters-degree of perceptual differentiation, stimulus format, and stimulus exposure duration-we show how different category-effects can be provoked in normal subjects on the same task. We interpret the results in light of the Pre-semantic Account of Category Effects (PACE; Gerlach, 2009), and conclude that category-effects do not reflect absolute processing differences between categories. Rather, category-effects are products of common operations which are differentially affected by the structural similarity among objects (with natural objects being more structurally similar than artefacts). The potentially most important aspect of the present study is the demonstration that category-effects are very context dependent; an aspect which has been neglected in earlier literature on category-specificity. PACE provides a useful framework in this respect, as it specifies how category-effects are influenced by changes in task and stimulus characteristics.